Sarcomatoid Carcinoma of the Prostate - Onur Açıkgöz; Eymen Gazel; Neslihan İnci Zengin; Yusuf Kasap; Ahmet Çamtosun; Ahmet Hamdi Yazıcıoğlu (Case Reports in Urology, 2013)
Sarcomatoid carcinoma of the prostate is among the rarest malignant neoplasm types and has been well known for its aggressive clinical course. Patient was admitted with the symptoms of lower urinary tract. Transurethral resection of prostate (TUR-P) was carried out. Revealing Gleason 5 + 3 = 8 prostate adenocarcinoma in TUR-P material. Thereby, a Radical Prostatectomy procedure was planned. In operation, frozen examination revealed adenocarcinoma metastasis to the obturator lymph node. The operation was terminated. In the postoperative 3rd month, the patient was re-admitted with acute urinary system symptoms. A cystoscopy performed and complete resection of the mass was performed. The pathological examination reported that the tumor was compatible with undifferentiated adenocarcinoma owing to presence of poorly differentiated tumoral cells and detection of adenocarcinoma in a relatively small (1%) focus. 4 month after the operation, the patient underwent another cyctoscopic examination which revealed the prostatic lounge and most of the bladder lumen to be filled with tumoral tissue. The tumoral tissues was resected incompletely. This material was diagnosed to be “Sarcomatoid Malignant Tumor” upon the new evidences of progressive dedifferentiation and predominant sarcomatoid appearance, compared with the former TUR-P materials. Subsequent PET-CT scan depicted multiple metastasis. The patient was referred to oncology department. In conclusion, sarcomatoid carcinoma is a malignant variant that brings along diagnostic and treatment difficulties.